Performance and quality of tall fescue (Festuca arundinacea Schreb.) and perennial ryegrass (Lolium perenne L.) and mixtures of both species grown with or without white clover (Trifolium repens L.) under cutting management. (9th December 2013) - Cougnon, M.; Baert, J.; Van Waes, C.; Reheul, D.
Abstract There is increasing interest in tall fescue (Festuca arundinacea Schreb.) in Western Europe and elsewhere, mainly because of its better drought resistance and yield potential compared with perennial ryegrass (Lolium perenne L.). Important drawbacks of tall fescue, compared with perennial ryegrass, are its lower digestibility and voluntary intake. Mixtures of both species might combine the advantages of each, and species interactions may eventually lead to transgressive overyielding. We compared the agronomic performance of tall fescue, perennial ryegrass and tall fescue–perennial ryegrass mixtures, as pure‐grass swards or in association with white clover (Trifolium repens L.). Tall fescue–perennial ryegrass mixtures differed in the proportion and ploidy of the perennial ryegrass component. Yield, feed quality and botanical composition were measured in the 3 years after the sowing year. We found significant effects of ploidy of the ryegrass variety and of the proportion of ryegrass in the initial seed mixture on the botanical composition of the swards. Nevertheless, all swards were dominated by tall fescue at the end of the experiment. No overyielding of the mixtures compared with that of single‐species swards was found, but feed quality was intermediate between that of the single‐species swards. Mixed swards had better drought resistance than L. perenne and higher feeding quality than F. arundinacea swards.